Implantation of collagen punctal plugs for the reduction of post-keratoplasty ametropia - Baskin, D; Waller, S (Nepalese Journal of Ophthalmology, 2010)
In 1995, a 46-year-old woman was referred for refractive surgery. Eleven years earlier, she had undergone an uncomplicated penetrating keratoplasty in her right eye to treat a dense corneal opacity caused by contact lens-related microbial keratitis. Due to high myopia in the graft, she was unable to achieve useful vision and declined contact lens use. After extensive counseling, she elected to undergo radial keratotomy (RK) and arcuate keratotomy (AK) in her right eye. We recommended the insertion of collagen punctal plugs into the keratotomy incisions to increase the RK effect. She also decided to have RK in her left eye. Postoperatively, her uncorrected visual acuity was 20/25 OD and 20/30 OS. We were able to contact her and her ophthalmologist eleven years later, and eight of eleven collagen plugs were still present in the incisions, with no signs of rejection or inflammation. Later, we learned that she underwent a repeat penetrating keratoplasty due to corneal graft failure after a phacoemulsification procedure. The pathologic examination of the intact plugs and graft also showed no rejection or inflammation. DOI: 10.3126/nepjoph.v1i1.3676 Nep J Oph 2009;1(1):72-74